ON THE SOUTH KANARA COASTAL FISHERY FOR MACKEREL, RASTRELLIGER CANAGURTA (CUVIER) TOGETHER WITH NOTES ON THE BIOLOGY OF THE FISH - Sekharan, K V (Indian Journal of Fisheries, 2015)
North of Mangalore, the South Kanara fishery for the Indian mackerel, Rastrelliger canagurta (Cuvier), is confined mostly to coastal waters, the gear used is the Rampant net, a large shore-seine which exploits only a narrow belt of the sea \-\\ miles from shore [see Pradhan (1956) for description and figure of the net]. The use of other gear for mackerel during the season has traditionally been under a social ban in many of the fishing villages; but even in other places, where the ban does not exist, no serious attempts are made to extend the area of operations. Nevertheless, the output at these centres of coastal fishing forms a major contribution to the total mackerel catch in India. As in other sections of the coast, the best catches are obtained during the October- December period, though the sea&on, as a rule, begins in October and lasts until March or April. During other months, small quantities of mackerel are caught in gill-nets (Pattavala) and small shore-seines (Kairampanis); the gill-net boats venture to a distance of about 6 miles off"shore, while ' Kairampanis' are operated within a zone of only about half a mile from the shore. Panikkar (1949, 1952) has summed up the present state of our knowledge regarding the life-history and movements of mackerel, and has further indicated the lines of investigation that have to be undertaken for a fuller understanding of the fluctuations in catches. Recently Pradhan (1956) has published the results of his study of the mackerel fishery of Karwar. This paper deals with the coastal fishery* of the region between Baikampady and Tarapathy in the South Kanara District,- with special reference to that of Malpe, one of most important mackerel centres on the West Coast.